Applying the technology acceptance model to online self-learning: A multigroup analysis - Juan Antonio Márquez García; Cristina Gallego Gómez; Alicia Tapia López; Matthew J. Schlosser (Journal of Innovation & Knowledge (JIK), 2024)
This study focuses on the structure of self-learning as a multidimensional construct, through competences such as autonomy and study planning of undergraduate students, over the last three years. The objective of this study, framed by Technology Acceptance Model (TAM), aims to gain insights into the acceptance of self-learning in online educational models within a post-pandemic, university context. More specifically and innovatively, this study sets out to explore gender differences in self-learning adoption, as previous studies have observed various findings. Action variables and motivation play crucial roles in self-learning. Davis's original TAM model (1989) put forward five key variables, all of which are dealt with both theoretically and practically in this study. Additionally, this study puts forward several hypotheses based on the TAM model, addressing perceived ease of use, perceived usefulness, attitude, user satisfaction and intention to use in the context of online learning. From a practical perspective, a multi-group analysis is carried out that has been applied to a sample made up of 313 male and female Spanish university students from different areas of knowledge. Questionnaires were conducted with all participants and statistics calculated; the results make it possible to affirm that the different dimensions of the self-learning structure are interrelated, and significant differences between men and women are observed in the adoption of the model. The study concludes that online education fosters a positive attitude toward self-learning in female students, unlike what happens with male students. While the sample size might be considered a limitation of the study, the study nonetheless observes that female students appear to be more inclined to develop a sense of self-learning. In contrast, male students - though consumers of self-learning - do not generate the same attitude. Therefore, the conclusion can be drawn that online teaching is a way to promote self-learning in women, which may inform universities when designing programs promoting student autonomy with new technologies.
Keywords: C; I; O; 650; Technology Acceptance Model (TAM); Self-learning; Gender; Multigroup analysis; Online teaching